2016
DOI: 10.1093/jjco/hyw090
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-induced chronic inflammatory demyelinating polyradiculoneuropathy mimicking rapid-onset Guillain–Barré syndrome: a case report

Abstract: Nivolumab, an anti-programmed death-1-specific monoclonal antibody, has demonstrated a durable response and effect on overall survival and has become one of the standard treatments for patients with advanced melanoma. Reported herein is a case of nivolumab-induced chronic inflammatory demyelinating polyradiculoneuropathy, in which an 85-year-old woman with stage IV melanoma developed grade 1 paresthesia 2 weeks after the initial dose of nivolumab was administered. With continued treatment, the neurological def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…Table details reports of associated melanoma and CIDP. There are a dozen reported cases of CIDP and melanoma, excluding patients who developed CIDP as a result of melanoma immunotherapy, vaccination by melonoma lysates, interferon α‐2b, and, more recently, immune check‐point inhibitors . With melanoma lysates and interferon α‐2b, implication of the melanoma appeared possible, particularly in the latter case because the patient had been untreated for 40 weeks before neurological presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Table details reports of associated melanoma and CIDP. There are a dozen reported cases of CIDP and melanoma, excluding patients who developed CIDP as a result of melanoma immunotherapy, vaccination by melonoma lysates, interferon α‐2b, and, more recently, immune check‐point inhibitors . With melanoma lysates and interferon α‐2b, implication of the melanoma appeared possible, particularly in the latter case because the patient had been untreated for 40 weeks before neurological presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported on acute or chronic demyelinating polyneuropathy induced by the treatment with immune checkpoint inhibitors 2 3. Tanaka et al 3 described a case of nivolumab-induced acute-onset chronic inflammatory demyelinating polyneuropathy (CIDP) relapsed by tapering corticosteroids after more than 6 months from onset. In our case, the neurological symptoms and electrophysiological findings dramatically improved by the administration of IVIg.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms experienced by our patient were so severe that we could hardly manage them, and we could not identify effective drugs to control them. Recently, Tanaka et al [7] reported the efficacy of intravenous immunoglobulin administration, with which we did not challenge our patient, for nivolumab-induced Guillain-Barré syndrome.…”
Section: Discussionmentioning
confidence: 60%
“…Of those, autoimmune encephalitis [6] and Guillain-Barré syndrome [7] have been reported as nivolumab-induced neuropathy; however, up of now, akathisia or akathisia-like neuropathy has not been reported. Symptoms experienced by our patient were so severe that we could hardly manage them, and we could not identify effective drugs to control them.…”
Section: Discussionmentioning
confidence: 99%